Challenges, barriers, and determinants of farmers’ adoption of agroecological practices in Tunisia: A Case study of Hamam biadha and Elles - Khader, Amina (2024)
Presentation on : Challenges, barriers, and determinants of farmers’ adoption of agroecological practices in Tunisia: A Case study of Hamam biadha and Elles.